Pengaruh Besarnya Sanksi Terhadap Tingkat Kepatuhan Pembayaran Pajak Kendaraan Bermotor Dengan Kepedulian Wajib Pajak Sebagai Variabel Moderasi : (Studi Pada Wajib Pajak Kendaraan Bermotor Di Kecamatan Tengaran) - Tiara Agusthine Kesia Sugianto; Theresia Woro Damayanti (Jurnal Akuntansi Profesi, 2022)
Abstract Tax is a contribution that must be paid by society which is compelling and its benefits will be enjoyed in the future. There are several factors that can affect the level of tax payment compliance, including tax witnesses and taxpayer concerns. The purpose of this study was to examine the effect of tax sanctions and taxpayer awareness on the level of compliance with motorized vehicle tax payments. This research was conducted by distributing questionnaires to taxpayers registered at the Samsat Tengaran Office using a purposive sampling method. Data analysis using regression test and Moderated Regression Analysis. The results of this study indicate that tax sanctions have a positive effect and taxpayer awareness has a positive effect on moderating the level of taxpayer compliance. Keywords: Motor Vehicle Tax, Tax Sanctions, Taxpayer Concerns, Tax Compliance